Leveraging Taiwan’s competency-based curriculum model: implications for low- and middle-income countries - Gulled Mohamed Yasin (Springer Nature, 2026)
This qualitative study examined how Taiwan’s 12-Year Basic Education Competency-Based Curriculum (CBC) was designed and implemented and what elements are transferable to low- and middle-income African contexts. The researcher triangulated five national policy/curriculum documents with 15 key-informant interviews (professors, principals, and policymakers) who had direct involvement in the CBC design, development and reforms and analyzed data using thematic analysis. In this regard, the research identified several core themes. A decentralized, bottom-up approach was fundamental, engaging a wide spectrum of stakeholders including educators, parents, industries, and communities in a multi-year co-design process. Competencies were contextualized from global frameworks (OECD DeSeCo) and systematically woven into both national mandates and school-based curricula to ensure local relevance. Implementation was underpinned by systemic, government-funded teacher professional development focused on shifting pedagogical practices and a move toward authentic assessment tools to measure holistic student growth. Furthermore, the curriculum was explicitly tailored to economic needs through strategic industry-education partnerships. Despite the participatory design, challenges included resistance from teachers accustomed to exam-centric instruction. The study concludes that Taiwan’s CBC is not a one-size-fits-all model but offers a transferable blueprint for context-responsive reform when adapted to local capacity, culture, and equity priorities.
This study explores Taiwan’s competency-based curriculum reform and draws out practical lessons for low- and middle-income countries, especially in Africa. It shows how stakeholder participation, teacher professional development, authentic assessment, and curriculum responsiveness to social and economic needs can support more context-sensitive and transferable curriculum reform.
Keywords: SOCIAL SCIENCES::Social sciences::Education; Curriculum reforms; Competency-based curriculum; Taiwan